SYSTEMATIC LITERATURE REVIEW: Model Pembelajaran Discovery Learning Untuk Meningkatkan Kemampuan Berpikir Kritis - Rosa Ary Ardhini; St. Budi Waluya; Mohammad Asikin; Zaenuri (Civiliza Publishing, 2021)
The purpose of this study is to determine the effect of the Discovery Learning model on students' mathematical critical thinking skills and to analyze indicators of critical thinking skills according to this literature review. The research method used is Systematic Literature Review or (SLR). This study traced 15 nationally accredited articles on Sinta 2 to Sinta 5 obtained from Google Scholar. The results showed that 1) The Discovery Learning model had a positive and significant impact on students' critical thinking skills in each educational unit, Elementary School , Junior High School, and Senior High School. 2) The application of the Discovery Learning model is able to improve students' critical thinking skills. 3) The indicators recommended to be used as a reference for students' critical thinking skills are (1) Identification, (2) Define, (3) Enumerate, (4) Analysis, (5) List, and (6) Self-correct.